Experimental Study on Properties of Rock-Cemented Coal Gangue-Fly Ash Backfill Bimaterials with Different Coal Gangue Particle Sizes - Yabo Wang; Dawei Yin; Shaojie Chen; Libo Zhang; Dongyi Liu; Yanhua Sun (Advances in Civil Engineering)
Properties of rock-cemented coal gangue-fly ash backfill (CGFB) bimaterials determine the effects of strip CGFB mining on controlling the surface subsidence in coal mines, which are affected by the coal gangue particle size in CGFB. In this paper, uniaxial compression tests were conducted on the coarse sandstone-CGFB composite samples with different coal gangue particle sizes, and their strength, acoustic emission (AE), and failure characteristics were investigated. The uniaxial compressive strength (UCS) and elastic modulus of the composite sample decreased with the coal gangue particle size. The strength of the composite sample is mainly dependent on that of CGFB in it, affected by interactions between CGFB and coarse sandstone. The deformation of the coarse sandstone weakened the damage accumulation within CGFB, resulting in the strength of the composite sample larger than that of CGFB. The average UCS values of composite samples with coal gangue particle sizes of 0∼5 mm, 5∼10 mm, and 10∼15 mm, increased by 10.78%, 14.98%, and 12.70% compared with CGFB in them, respectively. AE event signal regularity of the composite sample was divided into three stages: rising period, calm period, and active period. The intensity and frequency of AE event signals in three periods were strengthened with the coal gangue particle size. The calm period can be taken as the precursory information for the failure and instability of composite sample under loading, whose duration became shortly with the coal gangue particle size. The rebound deformation of coarse sandstone caused the fluctuations of AE event signals at the later stage of active period. The failures of the composite sample occurred within CGFB, and no obvious failures were found in the coarse sandstone. The CGFB mainly experienced the splitting failure accompanying by varying degrees of surface spalling failures. The broken degree of CGFB increased with the coal gangue particle size, and the largest weight ratio of CGFB fragments (chips) after failure was determined by the coal gangue particle size.